EFEKTIVITAS PENGGUNAAN MEDIA PEMBELAJARAN FLIPBOOK DIGITAL BERBASIS DISCOVERY LEARNING PADA MATERI SISTEM EKSKRESI MANUSIA - syam, sukmawati; Muhajirah Yunus, Nur (Universitas Cokroaminoto Palopo, 2024)
Flipbook learning media is a learning tool in electronic format that can display interactive simulations by combining several features in it, making students more interactive and learning more interesting. The aim of this research is to determine the effectiveness of using digital flipbook learning media based on Discovery Learning on Excretory System material, digital flipbook media based on Discovery Learning on Human Excretory System material. The type of research used was pre-experimental with a One Group Pretest Posttest Design. The sample for this research was class XI IPA 8 with 30 students selected using purposive sampling technique. The instrument of this research is a learning outcomes test. The research data were analyzed using descriptive statistical analysis. The results of the effectiveness test research showed that the mastery of learning outcomes was 76.67%. This criterion shows that digital flipbook learning media based on Discovery Learning is effective so that it can be used in Human Excretory System material.